Distinct and Coordinated Regulation of Small Non-coding RNAs by E2f1 and p53 During Drosophila Development and in Response to DNA Damage - Li, Dong; Ge, Ying; Zhao, Ze; Zhu, Rui; Wang, Xiang; Bi, Xiaolin (Frontiers in Cell and Developmental Biology, 2021)
Small non-coding RNAs (ncRNAs), including microRNAs (miRNAs) and PIWI-interacting RNAs (piRNAs), play a pivotal role in biological processes. A comprehensive quantitative reference of small ncRNAs expression during development and in DNA damage response (DDR) would significantly advance our understanding of their roles. In this study, we systemically analyzed the expression profile of miRNAs and piRNAs in wild-type flies, e2f1 mutant, p53 mutant and e2f1 p53 double mutant during development and after X-ray irradiation. By using small RNA sequencing and bioinformatic analysis, we found that both miRNAs and piRNAs were expressed in a dynamic mode and formed 4 distinct clusters during development. Notably, the expression pattern of miRNAs and piRNAs was changed in e2f1 mutant at multiple developmental stages, while retained in p53 mutant, indicating a critical role of E2f1 played in mediating small ncRNAs expression. Moreover, we identified differentially expressed (DE) small ncRNAs in e2f1 mutant and p53 mutant after X-ray irradiation. Furthermore, we mapped the binding motif of E2f1 and p53 around the small ncRNAs. Our data suggested that E2f1 and p53 work differently yet coordinately to regulate small ncRNAs expression, and E2f1 may play a major role to regulate miRNAs during development and after X-ray irradiation. Collectively, our results provide comprehensive characterization of small ncRNAs, as well as the regulatory roles of E2f1 and p53 in small ncRNAs expression, during development and in DNA damage response, which reveal new insights into the small ncRNAs biology.